2018
DOI: 10.1002/jccs.201700349
|View full text |Cite
|
Sign up to set email alerts
|

MNPs‐NHC6H4SO3H as high‐performance catalyst for the synthesis of 1,4‐diazepines containing tetrazole ring under microwave irradiation

Abstract: MNPs‐NHC6H4SO3H as an efficient catalyst was prepared and characterized by X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FT‐IR), scanning electron microscopy (SEM), vibrating sample magnetometer (VSM), DLS dynamic light scattering (DLS), and thermogravimetric analysis (TGA) techniques. The catalytic activity of MNPs‐NHC6H4SO3H was investigated in the synthesis of 1,4‐diazepines containing the tetrazole ring via a four‐component reaction under microwave irradiation. The heterogeneous catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this reaction cyclic imine is in situ generated and consumed (Scheme ). In addition, these tetrazole heterocyclic compounds were synthesized using the MNPs-NHC 6 H 4 SO 3 H and MCM-48/H 5 PW 10 V 2 O 40 catalysts. ,, …”
Section: Cyclic Imines In Azido−ugi Reactionsmentioning
confidence: 99%
“…In this reaction cyclic imine is in situ generated and consumed (Scheme ). In addition, these tetrazole heterocyclic compounds were synthesized using the MNPs-NHC 6 H 4 SO 3 H and MCM-48/H 5 PW 10 V 2 O 40 catalysts. ,, …”
Section: Cyclic Imines In Azido−ugi Reactionsmentioning
confidence: 99%
“…Quinolines are specic heterocyclic pharmacophores with diverse medicinal chemistry and several interesting pharmacological and therapeutic characteristics. [37][38][39] They are also used as the core moieties to prepare many well-known drugs with antifungal, antioxidant, and antituberculous activity (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Elemental analysis results showed that the content of nickel, aluminum, and oxygen in the NiAl 2 O 4 spinel nanocrystals was 48.56, 15.13, 36.31 (wt%), respectively. As a result of our great interest in preparation of heterocyclic compounds by applying heterogeneous catalysts, [26,27] herein we wish to report an efficient procedure to synthesize 2,3-dihydroquinazolin-4(1H)-one derivatives through a threecomponent one-pot condensation of isatoic anhydride, aromatic aldehyde, and primary amines/ or ammonium acetate using NiAl 2 O 4 spinel nanocrystals as catalysts under microwave irradiation (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%